Vulnerability to Downside Risk and Poverty in Vietnam - Felix Povel (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2010)
In this paper we propose a new measure of vulnerability called vulnerability to downside risk. The relevant benchmark for this new measure is the current level of wellbeing of a household as opposed to another benchmark such as the poverty line. We argue that this measure adds complementary information to existing measures such as Calvo and Dercon's (2007) axiomatic measure of vulnerability to poverty. We apply a measure of both vulnerability to downside risk and to poverty to data from Vietnam. We show that consumption smoothing capacities and the probability to experience an adverse event differ substantially between different wealth groups. Consequently, the relation between initial wealth and vulnerability to downside risk is highly non-linear. While moderately but not extremely poor households are relatively vulnerable to extreme poverty, they are less vulnerable to downside risk than any other group of households.
Keywords: D81; I31; I32; O12; 330; Vulnerability; Poverty; Shocks; Risk